2019
DOI: 10.14233/ajchem.2019.22118
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Aided Expedient Synthesis, Characterization and Antimicrobial Studies of Fluorenyl-Hydrazono-Thiazole Derivatives

Abstract: Ultrasound assisted facile synthesis of fluorenyl-hydrazonothiazoles (4a-d) in quantitative yields by the condensation of 2-(9H-fluoren-9-ylidene)hydrazinecarbothioamide (2) with substituted phenacyl bromides in presence of dimethyl formamide has been reported. The reaction of carbothioamide 2 with α-haloacids resulted in to fluorenyl-hydrazonothiazolidin-4-ones (3). The structural characterization of the cyclized products have been established by elemental analysis and spectral data (IR, NMR and mass). The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The ultrasonication gave the target products in higher yields and purity in shorter reaction times compared with the conventional method. [36,37] The biological results indicated that only compounds 35 and 36 displayed moderate biological activity against Gram-positive and Gram-negative bacteria, while fluorenyl-hydrazonothiazoles 37-38 present interesting antifungal activities (Table 12). 39a-f and 40a-f) by employing a one-pot multi-component approach.…”
Section: Methodsmentioning
confidence: 99%
“…The ultrasonication gave the target products in higher yields and purity in shorter reaction times compared with the conventional method. [36,37] The biological results indicated that only compounds 35 and 36 displayed moderate biological activity against Gram-positive and Gram-negative bacteria, while fluorenyl-hydrazonothiazoles 37-38 present interesting antifungal activities (Table 12). 39a-f and 40a-f) by employing a one-pot multi-component approach.…”
Section: Methodsmentioning
confidence: 99%